1735. The Pig Skin Commensal D. incerta Exhibits Antimicrobial Activity Against Methicillin-Resistant Staphylococcus aureus. (15th December 2022) - Wei, Monica; Knight, Simon; Flowers, Laurice; Walsh, Jasmine; Grice, Elizabeth A
Abstract: Background: Methicillin-resistant Staphylococcus aureus (MRSA) infections occur commonly on skin and cause significant healthcare burden. MRSA can also stably colonize the skin and nasal passages, contributing to community spread. This colonization results in long-term interaction with the skin microbiome, which harbors a diverse community of bacteria that often use antimicrobial molecules to compete for ecologic niches. We hypothesize that the skin microbiome contains bacteria that secrete novel antimicrobial agents against MRSA. Methods: Pigs are an established model organism for skin whose microbiome is not well explored. We mined the pig skin microbiome for bacterial species that inhibited MRSA via a modified disc diffusion assay. Results: We find that the novel pig skin commensal D. incerta inhibits USA300 strain MRSA via a secreted antimicrobial protein that can be isolated from cell-free supernatant. Analysis of the D. incerta genome shows little homology to known antimicrobial genes clusters. The identity of the antimicrobial molecule and whether its antimicrobial activity persists in the context of MRSA skin infection remain unclear. We characterize the identity of this antimicrobial molecule via parallel genomic and biochemical approaches. Finally, we propose to test the ability of D. incerta to impede MRSA colonization and improve healing of MRSA-mediated skin infection, two clinically important skin conditions. Conclusion: We screened the pig skin microbiome and successfully identified bacterial inhibitors of MRSA. Preliminary data suggest that the pig skin commensal D. incerta secretes a novel antimicrobial protein. Our current efforts focus on identifying this antimicrobial molecule and investigating its therapeutic potential in animal models of skin. Disclosures: All Authors : No reported disclosures.